Exploring the Relationship Between Coffee Shop Visitors' Coping Strategies and Well-Being - Maspul, Kurniawan Arif (Jurnal Psikologi, 2024)
This article investigates the relationship between coping strategies and the well-being of coffee shop visitors. Coffee shops serve as more than just places to get coffee; they provide individuals with a space to unwind, socialize, and cope with stress. Using a mixed-methods approach, including quantitative surveys and qualitative interviews, this study explores the experiences of visitors from different age groups in three coffee shops. The findings reveal that sensory engagement, visit duration, and the overall ambiance of coffee shops significantly contribute to emotional relaxation and well-being. Coffee shop owners can leverage these findings to create supportive environments that promote positive coping strategies and enhance the well-being of their customers. Further research is needed to validate these findings in different contexts and examine the long-term effects of coping strategies in coffee shop settings. Understanding the connection between coping strategies and well-being in coffee shop environments has implications for mental health promotion and the development of supportive spaces for individuals to cope with daily pressures.